2018
DOI: 10.2217/mmt-2017-0025
|View full text |Cite
|
Sign up to set email alerts
|

Interferon is Associated with Improved Survival for Node-Positive Cutaneous Melanoma: A Single-Institution Experience

Abstract: Aim:We assessed the role of adjuvant interferon on relapse-free survival (RFS), distant metastasis-free survival (DMFS) and overall survival (OS) in node-positive melanoma patients.Methods:We retrospectively reviewed 385 node-positive patients without distant metastatic disease treated from 1998 to 2015. The surgery was therapeutic lymph node dissection (LND, n = 86) or sentinel lymph node biopsy ± completion LND (n = 270). 128 patients (33.2%) received adjuvant interferon.Results:After a median follow-up of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Overall, the outcomes of 4 multicenter randomized controlled trials involving a total of 1916 patients supported the use of HDI as adjuvant therapy 25–27,47 . These studies demonstrated that HDI improved RFS in all 3 trials and overall survival (OS) in E1684 (compared with observation) and E1694 (vs. GMK) 29,30 . A subsequent meta-analysis, 29 of 14 randomized controlled trials of adjuvant IFN-α testing varying dose levels, regimens, and routes of administration indicated that adjuvant therapy with IFN-α reported a statistically significant improvement in both RFS and OS.…”
Section: Cytokine Immunotherapy: Interferon αmentioning
confidence: 97%
See 2 more Smart Citations
“…Overall, the outcomes of 4 multicenter randomized controlled trials involving a total of 1916 patients supported the use of HDI as adjuvant therapy 25–27,47 . These studies demonstrated that HDI improved RFS in all 3 trials and overall survival (OS) in E1684 (compared with observation) and E1694 (vs. GMK) 29,30 . A subsequent meta-analysis, 29 of 14 randomized controlled trials of adjuvant IFN-α testing varying dose levels, regimens, and routes of administration indicated that adjuvant therapy with IFN-α reported a statistically significant improvement in both RFS and OS.…”
Section: Cytokine Immunotherapy: Interferon αmentioning
confidence: 97%
“…[25][26][27]47 These studies demonstrated that HDI improved RFS in all 3 trials and overall survival (OS) in E1684 (compared with observation) and E1694 (vs. GMK). 29,30 A subsequent meta-analysis, 29 of 14 randomized controlled trials of adjuvant IFN-α testing varying dose levels, regimens, and routes of administration indicated that adjuvant therapy with IFN-α reported a statistically significant improvement in both RFS and OS. However, the clinical benefit was found to be minor (the hazard ratios [HRs] for disease recurrence and death were 0.82 and 0.89, respectively).…”
Section: Cytokine Immunotherapy: Interferon αmentioning
confidence: 99%
See 1 more Smart Citation
“…1215 These adjuvant therapies provided improved survival benefit as compared with observation or placebo, however, high rates of toxicities were significant concerns. 16,17 Recent studies have supported the adjuvant use of anti-PD1 monoclonal antibodies nivolumab and pembrolizumab as well as the combination of dabrafenib and trametinib (in patients with stage III BRAF-mutated melanoma). 1820 However, the relapse free survival for these patients is still poor, with median recurrence-free survival (RFS) of approximately 70–80% at year 1 and 50–60% at 3 years.…”
Section: Introductionmentioning
confidence: 99%